2003
DOI: 10.1080/10168730300000004
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology and Its Impact on Economic Growth and Productivity In Korea

Abstract: The purpose of this study is to examine the impact of IT on economic growth and productivity in Korea during the 1971-2000 periods. The growth contributions from standard input factors, IT capital inputs, and the business cycle effect are calculated on the basis of the growth accounting framework. The study also examines the source of productivity growth, using the extended growth model and drawing attention to the role that IT and knowledge capital may have played. The results show that IT capital contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Further, ICT connectivity in rural areas was intensified between 2000 and 2003. In 2000, 33 pilot community-based Internet Centres were developed nationwide (12 of which were in rural areas); with an additional 31 Internet / Information Centres established across the nation between 2001-03 (Economic Planning Unit reports, 2001& 2003; and an NITC Strategic Task Force, experimented with a Public-Private Partnership model for another 13 pilot projects nationally (John et al, 2004).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, ICT connectivity in rural areas was intensified between 2000 and 2003. In 2000, 33 pilot community-based Internet Centres were developed nationwide (12 of which were in rural areas); with an additional 31 Internet / Information Centres established across the nation between 2001-03 (Economic Planning Unit reports, 2001& 2003; and an NITC Strategic Task Force, experimented with a Public-Private Partnership model for another 13 pilot projects nationally (John et al, 2004).…”
Section: 2mentioning
confidence: 99%
“…The estimated result showed that ICT capital generated significant rate of return to the economy. Two years later, Kim (2003) examined the impact of ICT on productivity and economic growth in Korea during 1971 to 2000 sample period. The results showed that ICT capital contributed 16.3% to the output growth and has had strong positive effect on the growth of labor productivity in the long run.…”
Section: The Impact Of Ict On Economic Growth: a Reviewmentioning
confidence: 99%
“…Penggunaan teknologi tersebut sudah familiar dikalangan anggota masyarakat dapat mempengaruhi seluruh aspek kehidupan masyarakat di antaranya kegiatan bisnis (Amri & Surya, 2013). Teknologi informasi seperti halnya internet secara signifikan berkontribusi pada perkembangan dunia bisnis sebagai pilar utama pertumbuhan ekonomi suatu negara (Kim, 2003;Shahiduzzaman & Alam, 2014;Papaioannou & Dimelis, 2007). Penelitian empiris yang dilakukan oleh Erumban & Das (2016), Hodrab (2016) dan Kilic et al (2017) juga membuktikan bahwa teknologi informasi berdampak pada pertumbuhan ekonomi.…”
Section: Pendahuluanunclassified
“…Kuppusamy and Shanmugam (2007) examined the impact of ICT in Malaysia over the period , and found that ICT investment significantly improved the country's economic growth. On the Korean economy for the period 1971 to 2000, Kim (2003) found that ICT capital had a strong positive effect on the growth of labour productivity in the long run, while contributing 16.3% to the growth in output.…”
Section: Empirical Investigationsmentioning
confidence: 99%